Revisão taxonômica de Tometes Valenciennes, 1850 (Characiformes: Serrasalmidae) das drenagens do Escudo das Guianas - ANDRADE, Marcelo Costa (Universidade Federal do Pará, 2014)
The genus Tometes Valenciennes, 1850 was originally described for the typespecies T. trilobatus, by presenting incisiform and bi- tricuspid teeth. However, the genus was synonymized with Myleus Müller and Troschell, 1844 for approximately a century and a half until being revalidated with an addition of two new species descriptions, T. lebaili and T. makue. This study presents a taxonomic review of Tometes from Guyana Shield where the three nominal species are recognized as valid and here were re-described, also a new species from Trombetas basin was described, increasing the diversity and distribution of genus. Among the main characteristics of diagnosis were observed: T. trilobatus is distinguishes from its congeners by having dentary and premaxillary teeth with the central cusp with rounded edge (vs. teeth with the central cusp or principal cusp with sharp edge). T. lebaili differs from others Tometes by having mouth oblique dorsally directed (vs. terminal mouth). T. makue is different by having a few spines on the serrae prepelvic, always between 0 and 9 spines (vs. over 9 spines). Already the new species is distinguished by the neurocranium with a slight concavity at the level of the epiphyseal bar, and also by having scales of irregular size (vs. dorsal profile of the neurocranium without a slight concavity, and scales of regular size). All species of Tometes are strictly rheophilic, and occur exclusively in the rapids of shield rivers, complex and fragile biotopes that are threatened by anthropogenic activities. The conclusions reached by this study highlight the urgent challenge to understand more fully existing species/habitat relationships.